(untitled) (Observatorio Económico, 2016)
The Atmospheric Decontamination Plan for the Metropolitan Region, known as “Santiago Respira” (“Santiago Breathes”), has as its primary objective reducing emissions of fine particulate matter, known as PM2.5, in the Metropolitan Region (RM), in view of its especially harmful impact on human health. The plan is currently undergoing public consultation (until March 30, 2016), and the first measures are expected to take effect by the middle of this year. Continue reading...